2014
DOI: 10.1155/2014/891934
|View full text |Cite|
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Induced Toxicity in Human Lung Cells: Role of ROS Mediated DNA Damage and Apoptosis

Abstract: Cerium oxide nanoparticles (CeO2 NPs) have promising industrial and biomedical applications. In spite of their applications, the toxicity of these NPs in biological/physiological environment is a major concern. Present study aimed to understand the molecular mechanism underlying the toxicity of CeO2 NPs on lung adenocarcinoma (A549) cells. After internalization, CeO2 NPs caused significant cytotoxicity and morphological changes in A549 cells. Further, the cell death was found to be apoptotic as shown by loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 58 publications
8
121
3
2
Order By: Relevance
“…Finally, cell line characteristics such as p53 status or tumoral origin can also influence the role of CeO 2 -NP as cytotoxic ) by accumulating hydroxyl ions over superoxide radicals in acidic pH potentiating cancer cell apoptosis, due to its valence-state oscillations (Asati et al 2009). In this context, a recent study showed data in a tumoral lung cell line (A549) wherein apoptotic cell death via ROS-mediated DNA damage and cell cycle arrest, as well as morphological changes, were observed (Mittal and Pandey 2014). This would emphasize the importance of the cell line used to determine the toxicity of NP, including CeO 2 -NP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, cell line characteristics such as p53 status or tumoral origin can also influence the role of CeO 2 -NP as cytotoxic ) by accumulating hydroxyl ions over superoxide radicals in acidic pH potentiating cancer cell apoptosis, due to its valence-state oscillations (Asati et al 2009). In this context, a recent study showed data in a tumoral lung cell line (A549) wherein apoptotic cell death via ROS-mediated DNA damage and cell cycle arrest, as well as morphological changes, were observed (Mittal and Pandey 2014). This would emphasize the importance of the cell line used to determine the toxicity of NP, including CeO 2 -NP.…”
Section: Discussionmentioning
confidence: 99%
“…From this result, it has been found that nanoceria had the ability of free-radical scavenging, which created a precedent of nanoceria in biological applications and greatly inspired the people of research interest. Until now, there have been many studies on the toxicity properties of nanoceria coated with polymers (dextran, PEG, chitosan, heparin, PAA, and PVP) within the range of 3-20 nm as demonstrated in Figure 4 against cancer cells (lung, breast, ovary, osteosarcoma, and pancreas) and healthy cells (dermal fibroblasts, endothelial cell, keratinocytes, human monocytes, and macrophages) [25][26][27][28][29]. All these researches have laid a foundation for study of antioxidant property.…”
Section: Controllable Synthesis Of Nanoceriamentioning
confidence: 99%
“…CONPs have also shown to be effective in protecting adult cardiac progenitor cells against ROS‐induced stress,9 and in reducing inflammation and radiation‐induced damage in internal organs in mice 10. On the other hand, some studies have reported controversial effects of CONPs; when applied to human lung epithelial cells, adverse cellular responses including increased ROS, induction of oxidative‐stress genes, and apoptotic cell death were observed 11. This is primarily due to the different (possibly higher) doses used and the variable oxidation/reduction state of the CONPs as well as the cell‐dependent responses of nanoparticles such as endocytic activity and toxicity sensitivity.…”
Section: Introductionmentioning
confidence: 99%